Mitigation of Ionizing Radiation-Induced Gastrointestinal Damage by Insulin-Like Growth Factor-1 in Mice - Pejchal, Jaroslav; Tichy, Ales; Kmochova, Adela; Fikejzlova, Lenka; Kubelkova, Klara; Milanova, Marcela; Lierova, Anna; Filipova, Alzbeta; Muckova, Lubica; Cizkova, Jana (Frontiers in Pharmacology, 2022)
Purpose: Insulin-like growth factor-1 (IGF-1) stimulates epithelial regeneration but may also induce life-threatening hypoglycemia. In our study, we first assessed its safety. Subsequently, we examined the effect of IGF-1 administered in different dose regimens on gastrointestinal damage induced by high doses of gamma radiation. Material and methods: First, fasting C57BL/6 mice were injected subcutaneously with IGF-1 at a single dose of 0, 0.2, 1, and 2 mg/kg to determine the maximum tolerated dose (MTD). The glycemic effect of MTD (1 mg/kg) was additionally tested in non-fasting animals. Subsequently, a survival experiment was performed. Animals were irradiated (60Co; 14, 14.5, or 15 Gy; shielded head), and IGF-1 was administered subcutaneously at 1 mg/kg 1, 24, and 48 h after irradiation. Simultaneously, mice were irradiated (60Co; 12, 14, or 15 Gy; shielded head), and IGF-1 was administered subcutaneously under the same regimen. Jejunum and lung damage were assessed 84 h after irradiation. Finally, we evaluated the effect of six different IGF-1 dosage regimens administered subcutaneously on gastrointestinal damage and peripheral blood changes in mice six days after irradiation (60Co; 12 and 14 Gy; shielded head). The regimens differed in the number of doses (one to five doses) and the onset of administration (starting at 1 [five regimens] or 24 h [one regimen] after irradiation). Results: MTD was established at 1 mg/kg. MTD mitigated lethality induced by 14 Gy and reduced jejunum and lung damage caused by 12 and 14 Gy. However, different dosing regimens showed different efficacy, with three and four doses (administered 1, 24, and 48 hours and 1, 24, 48, and 72 hours after irradiation, respectively) being the most effective. The three-dose regimens supported intestinal regeneration even if the administration started at 24 h after irradiation, but its potency decreased. Conclusion: IGF-1 seems promising in the mitigation of high-dose irradiation damage. However, the selected dosage regimen affects its efficacy.